Assessing the impacts of industrial digitization on synergistic effects of pollution and carbon reduction - Zhang, Liyao; Diao, Yanxia; Chen, Yiming; Ma, Tao (Frontiers in Environmental Science, 2025)
Synergistic effects of pollution and carbon reduction forms the core of ecological civilization construction in the “14th Five-Year Plan” period. Based on the panel data of prefecture-level cities in China from 2012 to 2023, first, the baseline regression model and the spatial panel Durbin model are used to discuss the direct and spatial effects of industrial digitization on synergistic effects of pollution and carbon reduction. Second, based on whole-process management, through the construction of a multiple intermediary effects model, the indirect impact of industrial digitization on synergistic effects of pollution and carbon reduction was explored. Third, heterogeneity tests from multiple perspectives are conducted. It is found that: (1) industrial digitalization has a remarkable positive impact on synergistic effects of pollution and carbon reduction, and there is a positive spillover effect. (2) Industrial digitization can indirectly promote synergistic effects of pollution and carbon reduction by strengthening “Source prevention” through renewable energy substitution, enhancing “process control” through green process innovation, and strengthening “end-of-pipe treatment” through environmental regulations. (3) Industrial digitization has a more remarkable promoting effect on synergistic effects of pollution and carbon reduction in energy basins, higher-level cities, large cities, and urban agglomerations. The research conclusions promote traditional industries to use the “digital cloud” to help the combined development of pollution and carbon reduction and offer a scientific foundation and theoretical reference for promoting industrial digitization to empower synergistic effects of pollution and carbon reduction.